2020
DOI: 10.3390/molecules25092109
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Cleavage of β-O-4 Ether Bonds in Lignin over Ni/TiO2

Abstract: It is of great importance to explore the selective hydrogenolysis of β-O-4 linkages, which account for 45–60% of all linkages in native lignin, to produce valued-added chemicals and fuels from biomass employing UV light as catalyst. TiO2 exhibited satisfactory catalytic performances in various photochemical reactions, due to its versatile advantages involving high catalytic activity, low cost and non-toxicity. In this work, 20 wt.% Ni/TiO2 and oxidant PCC (Pyridinium chlorochromate) were employed to promote th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Chemie strates 4-8 was previously explored with different photocatalysts, [40] among them at ype of heteroleptic cyclometalated iridium(III) complex for which subsequent mechanistic studies demonstrated that in the presence of large excess of tertiary amine as sacrificial electron donor, the initial iridium-(III) complex is first converted to another iridium(III) compound, [40b] which is then the actual catalytically active species. [8,42] Here,i nt he case of the PDI dianions,t he lignin model substrate photocleavage seems to occur via am ore straightforward mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Chemie strates 4-8 was previously explored with different photocatalysts, [40] among them at ype of heteroleptic cyclometalated iridium(III) complex for which subsequent mechanistic studies demonstrated that in the presence of large excess of tertiary amine as sacrificial electron donor, the initial iridium-(III) complex is first converted to another iridium(III) compound, [40b] which is then the actual catalytically active species. [8,42] Here,i nt he case of the PDI dianions,t he lignin model substrate photocleavage seems to occur via am ore straightforward mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, moderate amounts of methoxy-substituted aromatic rings were detected, which was consistent with the results in Table . β-O-4 model compounds with γ-OH could represent the lignin typical realistic segment . Therefore, 2-(2-methoxyphenoxy)-1-(4-methoxyphenyl)­propane-1,3-diol was selected as a model compound and tp afford 42, 40, and 8% yields of 1-methoxy-4-propylcyclohexane, 2-methoxycyclohexan-1-ol, and cyclohexanol, respectively (Table entry 6).…”
Section: Results and Discussionmentioning
confidence: 99%
“…[39] To test this concept, we investigated the visible-light-mediated C a À Ob ond cleavage in small molecules resembling the lignin biopolymer (Table 3). This reaction requires fairly negative reduction potentials, [40] and it is of interest from an application-oriented perspective in which the controlled depolymerization of lignin would lead to useful commodity products. [40b,41] Substrates 4-8 (Table 3) were dissolved along with 1mol %o fP DI(H)-dipp in acetonitrile,a nd then am ixture of Na 2 S 2 O 4 (3 equivalents) and tetra-n-butylammonium chloride (TBACl, 0.2 equivalents) in water was added under oxygen-free conditions (SI page S38).…”
Section: Methodsmentioning
confidence: 99%
“…Forschungsartikel strates 4-8 was previously explored with different photocatalysts, [40] among them at ype of heteroleptic cyclometalated iridium(III) complex for which subsequent mechanistic studies demonstrated that in the presence of large excess of tertiary amine as sacrificial electron donor, the initial iridium-(III) complex is first converted to another iridium(III) compound, [40b] which is then the actual catalytically active species. [8,42] Here,i nt he case of the PDI dianions,t he lignin model substrate photocleavage seems to occur via am ore straightforward mechanism.…”
Section: Angewandte Chemiementioning
confidence: 99%